Risk assessment of glycoalkaloids in feed and food, in particular in potatoes and potato‐derived products. (11th August 2020) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; et al.
Abstract: The European Commission asked EFSA for a scientific opinion on the risks for animal and human health related to the presence of glycoalkaloids (GAs) in feed and food. This risk assessment covers edible parts of potato plants and other food plants containing GAs, in particular, tomato and aubergine. In humans, acute toxic effects of potato GAs (α‐solanine and α‐chaconine) include gastrointestinal symptoms such as nausea, vomiting and diarrhoea. For these effects, the CONTAM Panel identified a lowest‐observed‐adverse‐effect level of 1 mg total potato GAs/kg body weight (bw) per day as a reference point for the risk characterisation following acute exposure. In humans, no evidence of health problems associated with repeated or long‐term intake of GAs via potatoes has been identified. No reference point for chronic exposure could be identified from the experimental animal studies. Occurrence data were available only for α‐solanine and α‐chaconine, mostly for potatoes. The acute dietary exposure to potato GAs was estimated using a probabilistic approach and applying processing factors for food. Due to the limited data available, a margin of exposure (MOE) approach was applied. The MOEs for the younger age groups indicate a health concern for the food consumption surveys with the highest mean exposure, as well as for the P95 exposure in all surveys. For adult age groups, the MOEs indicate a health concern only for the food consumption surveys with the highest P95 exposures. For tomato and aubergine GAs, the risk to human health could not be characterised due to the lack of occurrence data and the limited toxicity data. For horses, farm and companion animals, no risk characterisation for potato GAs could be performed due to insufficient data on occurrence in feed and on potential adverse effects of GAs in these species. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2020.EN-1905/full